Analisis Sarana Prasarana dan Fasilitas Pendukung untuk Memasarkan Destinasi Wisata di Kabupaten Nias Barat - Daeli, Ferjenian Marlin; Saragih, Agus Mariani (BUDGETING : Journal of Business, Management and Accounting, 2024)
Infrastructure facilities are everything that supports the ease of participants to take part in tourism activities starting from starting to the completion of the organization of these tourism activities. The purpose of this study was to determine the availability of infrastructure and supporting facilities to market tourist destinations in West Nias Regency. The research method used is descriptive qualitative with direct observation data collection to West Nias Regency. As well as conducting interviews with the Hotel and the Office of Youth Sports Culture and Tourism. The results obtained that the components of infrastructure and supporting facilities have all been fulfilled, only still need improvement from the aspects of accessibility, transportation equipment, security facilities, finance, health, information centers, venues, capacity, layout, atmosphere, service, security, availability. While tourist destinations in West Nias Regency have all been fulfilled, only still need improvement from the aspects of accessibility, attractions, amenity, and human resources (Human Resources). Based on the results of calculations using the SWOT approach, it can be concluded that the infrastructure and supporting facilities for marketing tourist destinations in West Nias Regency are in quadrant I position, thus showing a very favorable situation for West Nias Regency to carry out an aggressive/growth strategy. Keywords: Infrastructure, Tourism Destinations, SWOT.